URETHRAL STRICTURES (World Bulletin of Public Health, 2024)
The urethra is a narrow tube that carries urine from the bladder out of the body. Urethral strictures occur when a portion of the urethra becomes scarred and narrowed, restricting the flow of urine. This common urological condition can develop for various reasons and significantly impact a patient's quality of life if left untreated. This article aims to provide a comprehensive overview of urethral strictures, exploring their causes, clinical manifestations, and modern treatment approaches